1977
DOI: 10.1159/000198004
|View full text |Cite
|
Sign up to set email alerts
|

Massive Pancreatic Ascites without Carcinoma Report of Three Cases

Abstract: Three cases of benign pancreatic ascites have been added to 94 cases reviewed from the literature. Common characteristics of this syndrome were chronic alcoholism, intermittent abdominal pain, nausea, vomiting and considerable weight loss which occurred despite fluid accumulation. Markedly elevated protein and amylase levels in the ascitic fluid, hyperamylasemia and hypoalbuminemia were the major diagnostic clues as to the pancreatic origin of ascites. Predominant pathological findings were chronic pancreatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In a report of 96 cases of pancreatic ascites, the majority (n = 74) of cases described the ascitic fluid as amber-colored. [5] Other imaging that may be used to diagnose pancreatic ascites includes CT scan or ERCP to evaluate for pancreatitis or pseudocyst. ERCP is particularly beneficial as it is both diagnostic and therapeutic; after imaging, stent placement may occlude the disruption.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In a report of 96 cases of pancreatic ascites, the majority (n = 74) of cases described the ascitic fluid as amber-colored. [5] Other imaging that may be used to diagnose pancreatic ascites includes CT scan or ERCP to evaluate for pancreatitis or pseudocyst. ERCP is particularly beneficial as it is both diagnostic and therapeutic; after imaging, stent placement may occlude the disruption.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…There have been reports of blunt abdominal trauma which led to pancreatic pseudocyst formation and pancreatic ascites, and even fewer reports of iatrogenic pancreatic ascites. [5] It has been reported that traumatic pancreatic ascites has a faster onset (several weeks to several months) than non-traumatic pancreatic ascites (several weeks to one year). [5] Iatrogenic pancreatic ascites is a rarely reported event.…”
Section: Black Appearancementioning
confidence: 99%
See 1 more Smart Citation